2014
DOI: 10.1179/1754762813y.0000000060
|View full text |Cite
|
Sign up to set email alerts
|

Aural rehabilitation in children with cochlear implants: A study of cognition, social communication, and motor skill development

Abstract: Cochlear implantation and aural rehabilitation may result in accelerated rates of cognition, social communication, and motor skill development in deaf children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Children who are born deaf and do not have access to language, whether spoken or signed, in early life are shown to have deficits in social communication and in cognition and motor development 23. Previous research suggests that early implantation, under the age of 3, paired with training and access to spoken language is paramount for reaching the developmentally important milestones necessary to catch up with typically developing peers who have been exposed to language since birth 14 23–25.…”
Section: Discussionmentioning
confidence: 99%
“…Children who are born deaf and do not have access to language, whether spoken or signed, in early life are shown to have deficits in social communication and in cognition and motor development 23. Previous research suggests that early implantation, under the age of 3, paired with training and access to spoken language is paramount for reaching the developmentally important milestones necessary to catch up with typically developing peers who have been exposed to language since birth 14 23–25.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to children with SNHL [23], better outcomes in children with ANSD are associated with receiving hearing interventions (CIs or HAs) before three years of age [20,24,25]. While existing evidence demonstrates the benefits of CIs for both children with SNHL and ANSD [7,17,[26][27][28][29], factors with prognostic value for intervention outcomes have been less studied [24,30,31]. This matched case-control study had two main objectives: 1) To compare children with ANSD and SNHL in open-set speech perception test scores through a matched case-control study design (1:2 ratio), and 2) To identify factors that show predictive value for post-CI speech perception outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Aural rehabilitation for children who receive CIs is an integral component of the implant process; without proper auditory training, the benefit obtained from CI could be reduced. It has been demonstrated that both children and adults may benefit from structured aural rehabilitation programs that offer auditory training and strategies to maximize the benefits achieved from implantation (Heydebrand et al, 2005;Jeddi et al, 2014). Previous studies suggested that using a computeraided training could facilitate the rehabilitation process, which may optimize the implantation outcome (Sweetow and Palmer, 2005;Wu et al, 2007).…”
mentioning
confidence: 99%